We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
45
1
avatar

Find p+q, given that (q+4)(p+3)-(q+2)(p+1)=44.

 Nov 24, 2019
 #1
avatar
0

Hence, 

First multiply 

(q+4)(p+3) 

then multiply

(q+2)(p+1) 

 

Subtract them and solve the equation 

 

Solution:
 

(q+4)(p+3)=qp+3q+4p+12

(q+2)(p+1)=qp+q+2p+2 

Subtract

 

qp+3q+4p+12-(qp+q+2p+2)

 

qp+3q+4p+12-qp-q-2p-2

2q+2p+10=44  subtract 10

2q+2p=34

Divide by 2 

q+p=17

 Nov 24, 2019

22 Online Users

avatar